Determination of Some Chemicals Compounds in the water system of the Al-Ramadi teaching hospital for maternity and children - Abdullah, Saja; Mahmood, Bashar (Iraqi Journal of Civil Engineering, 2023)
ABSTRACT. Hospitals pose a significant risk to human health due to the contamination of their environment with chemical elements. Exposure to these elements can have adverse health effects, such as neurological and developmental problems, cancer, and endocrine disruptors. To prevent and mitigate the risks associated with contamination, it is important to identify and control the sources of contamination. This study intends to investigate how chemical elements are contaminating hospitals, including the sources of contamination, possible health impacts of exposure, and preventative and remedial actions that may be done to lessen the dangers. To reach the aims of this study, water samples from three different spots at two different seasons (winter and summer) of the water flow through the hospitals (Hospital water on its first entry inside, Wastewater after use inside and around the hospital and Wastewater after passing through the treatment unit inside the hospital) have been collected. Magnetic suspended matter (TS), Total materials (T.D.S), Electrical Conductivity, and Turbidity tests have been done to the collected water samples. Additionally, heavy materials have been detected in the collected samples. The results showed that the pH function increased slightly and insignificantly for the alkaline after using the water, while the water conductivity, Alkalinit, hardness, and percentage of suspended solids (T.S.S) and dissolved solids (TDS) reached the highest in wastewater. From the results of this study, we can conclude that the stages of treatment are slow and inefficient.